Chemical and Organoleptic Properties of Dragon Fruit Gummy Candy and Apple Snail Collagen Extract with Carrageenan Addition - Ramadhanty, Arlita; Rosida, Dedin Finatsiyatull; Yulistiani, Ratna (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Gummy candy is a soft confectionery crafted from fruit juice, sugar, and gelling agents, known for its chewy texture. The utilization of dragon fruit juice enhances its nutritional value due to its antioxidant properties, phenolic compounds, and vitamin C content. Additionally, it aims to diversify products derived from dragon fruit. Meanwhile, the utilization of collagen from apple snails seeks to boost the economic value of these snails and provide an alternative source of collagen raw material. In this study, the gummy candy uses carrageenan as a hydrocolloid material to establish the chewy texture. This study's primary objective is to determine the optimal combination involving the proportion of dragon fruit juice, apple snail collagen extract, and carrageenan concentration for producing high-quality gummy candy. The research employed a Completely Randomized Design (CRD) with a two-factor factorial pattern and two replications. The first factor was the proportion of dragon fruit juice to apple snail collagen (70:30, 75:25, and 80:20), while the second factor was the carrageenan concentration (3%, 5%, and 7% w/w). Observational data were analyzed using Analysis of Variance (ANOVA), and if interactions were observed, they were further assessed with Tukey's test at a significance level of 5%. The treatment combination of a 75:25 proportion of dragon fruit juice to apple snail collagen and a 7% carrageenan concentration proved to be the most effective, yielding gummy candy with a moisture content of 13.21%, ash content of 0.95%, and organoleptic evaluation scores for aroma, taste, color, and texture of 3.25, 3.4, 3.4, and 3.7.